Strategi Pemasaran Guardian Ramayana Kota Serang Dalam Meningkatkan Penjualan Produk Wardah - Dewi Ilma Agustin; Rosanti; Uswatun Hasanah; Ani Gusliyani; April Laksana (Universitas Sains dan Teknologi Komputer, 2024)
The cosmetic industry is currently experiencing rapid growth and intense competition in the personal care and cosmetic market, both domestically and internationally. Purchasing decisions for cosmetics are influenced by various factors, including price, product quality, and advertising. In this era of globalization, companies face opportunities and challenges from external and internal factors. Marketing plays a crucial role in achieving company success by satisfying consumer needs. Implementing marketing strategies that consider the four elements of the marketing mix product, price, place, and promotion along with a SWOT analysis is necessary to adjust to changes in the market.. This research focuses on Guardian, a leading health and beauty retailer in Indonesia, specifically analyzing the marketing strategies of Wardah cosmetic products. Through qualitative descriptive research, including direct interviews with experts in the field, The analysis uncovers the strengths, weaknesses, opportunities, and threats of Wardah, along with its strategies related to the 4P strategies. Key findings highlight the strong brand reputation, challenges of price competition, and the continuous need for product innovation and market adaptation. By optimizing strengths, addressing weaknesses, leveraging opportunities, and anticipating threats, Wardah can enhance its marketing strategy at Guardian Ramayana Serang and maintain its competitive position in the cosmetic market. Effective marketing strategy integration, such as direct distribution, careful price monitoring, and diverse promotional channels, provides a solid foundation for Wardah's sustainable growth and positive image in the cosmetic market.